2010
DOI: 10.1073/pnas.1012561107
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of isoprene-derived organosulfates to free tropospheric aerosol mass

Abstract: Recent laboratory studies have demonstrated that isoprene oxidation products can partition to atmospheric aerosols by reacting with condensed phase sulfuric acid, forming low-volatility organosulfate compounds. We have identified organosulfate compounds in free tropospheric aerosols by single particle mass spectrometry during several airborne field campaigns. One of these organosulfates is identified as the sulfate ester of IEPOX, a second generation oxidation product of isoprene. The patterns of IEPOX sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
242
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(260 citation statements)
references
References 42 publications
13
242
0
Order By: Relevance
“…The PALMS instrument observed that the isoprene-derived organosulfate, IEPOX sulfate ester, comprised <0.01% of submicron aerosol mass in Pasadena, which supports the negligible role of organosulfates in this location. (Note: The mass abundance for the IEPOX sulfate ester was determined using detailed laboratory calibrations that were performed for a previous study [Froyd et al, 2010].) Furthermore, FTIR measurements of organonitrates [Day et al, 2010] found that concentrations were less than 2% of the measured nitrate (by AMS) on average, which is much lower than the percentage estimated in Riverside (10%).…”
Section: Discussionmentioning
confidence: 99%
“…The PALMS instrument observed that the isoprene-derived organosulfate, IEPOX sulfate ester, comprised <0.01% of submicron aerosol mass in Pasadena, which supports the negligible role of organosulfates in this location. (Note: The mass abundance for the IEPOX sulfate ester was determined using detailed laboratory calibrations that were performed for a previous study [Froyd et al, 2010].) Furthermore, FTIR measurements of organonitrates [Day et al, 2010] found that concentrations were less than 2% of the measured nitrate (by AMS) on average, which is much lower than the percentage estimated in Riverside (10%).…”
Section: Discussionmentioning
confidence: 99%
“…From single particle mass spectrometric measurements IEPOX sulfate esters were identified in 80 % and 50 % of the analyzed particles measured at altitudes of 5 and 10 km in the tropical free troposphere, respectively (Froyd et al, 2010). In the boundary layer, IEPOX sulfate ester in aerosol particles did not occur.…”
mentioning
confidence: 93%
“…In the boundary layer, IEPOX sulfate ester in aerosol particles did not occur. This is explained by a low abundance of acidic aerosol particles acting as seed particles and with a relatively short time since the emission of isoprene (Froyd et al, 2010). However, with lofting of isoprene and its derivatives 35 above the boundary layer, it is suggested that IEPOX can partition more efficiently to acidic aerosol particles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SOA has been implicated in cardiovascular disease (Pope III and Dockery, 2006) and as an important driver of climate change (Hallquist et al, 2009). Seven different chemically distinct compounds based on the isoprene carbon backbone, containing epoxy, alcohol, nitrate, and/or sulfate functional groups, have now been identified in ambient SOA Claeys et al, 2004;Wang et al, 2005;Surratt et al, 2007;Altieri et al, 2009;Gómez-González et al, 2008;Surratt et al, 2008;Froyd et al, 2010). Some of these compounds are undoubtedly formed from gas phase processing (Perring et al, 2009a, b;Lockwood et al, 2010;Ng et al, 2008), of isoprene, while other compounds (such as organosulfates) clearly indicate that additional chemical processing is occurring on ambient SOA particles themselves (Cole-Filipiak et al, 2010;Paulot et al, 2009;Surratt et al, 2010;Chan et al, 2010;Minerath et al, 2008Eddingsaas et al, 2010;Szmigielski et al, 2010;Nozière et al, 2010;Rudzinski et al, 2009) We recently investigated some of the potential SOA-phase chemistry for isoprene-related compounds, and proposed an overall mechanism (shown in Fig.…”
Section: Introductionmentioning
confidence: 99%